Mode of First Delivery and Women's Intentions for Subsequent Childbearing: Findings from the First Baby Study. Issue 1 (22nd November 2012) - Kjerulff, Kristen H.; Velott, Diana L.; Zhu, Junjia; Chuang, Cynthia H.; Hillemeier, Marianne M.; Paul, Ian M.; Repke, John T.
Abstract Background More than a dozen studies have reported a reduced rate of childbearing after caesarean delivery (CD). It has been hypothesised that this is because women who deliver by CD are less likely to intend to have subsequent children than women who deliver vaginally – either before childbirth or as a consequence of CD. Little research has addressed either of these hypotheses. Methods As part of an ongoing prospective study, we interviewed 3006 women in their third trimester and 1 month after first childbirth to assess subsequent childbearing intentions. Results Women who delivered by CD were similar to those who delivered vaginally in intent to have at least one additional child, both before childbirth (90.1% vaginal, 89.9% CD; P = 0.97) and after (87.8% vaginal, 87.1% CD; P = 0.87); however, women who had CD were less likely to intend two or more additional children, both before childbirth (34.7% vaginal, 29.2% CD; P = 0.03) and after (32.2% vaginal, 26.1% CD; P = 0.01). Among women who intended to have at least one additional child before childbirth, 5.0% reported intending to have no additional children 1 month after delivery (5.1% vaginal, 4.6% CD; P = 0.52). Conclusions Women whose first delivery is by CD are less likely to intend a relatively large family of three or more children than those who deliver vaginally, but delivery by CD does not decrease women's intentions to have at least one more child any more than does vaginal delivery, at least in the short term.